2018
DOI: 10.1074/jbc.ra117.000880
|View full text |Cite
|
Sign up to set email alerts
|

Probing the quality control mechanism of the Escherichia coli twin-arginine translocase with folding variants of a de novo–designed heme protein

Abstract: Protein transport across the cytoplasmic membrane of bacterial cells is mediated by either the general secretion (Sec) system or the twin-arginine translocase (Tat). The Tat machinery exports folded and cofactor-containing proteins from the cytoplasm to the periplasm by using the transmembrane proton motive force as a source of energy. The Tat apparatus apparently senses the folded state of its protein substrates, a quality-control mechanism that prevents premature export of nascent unfolded or misfolded polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…It should be noted that we have not tested the 'quality'of the exported proteins, in terms of folding delity or activity. However, several heterologous proteins (including an scFv)have been exported by Tat and shown to be active in previous studies [7,11,12,13] and there is no obvious reason why export mediated by the PhoDn signal should be different. Moreover, a range of studies have shown that the Tat system is predisposed to export correctly folded proteins [5][6][7][8][9][10][11][12][13][14][15][16][17][18]10].…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that we have not tested the 'quality'of the exported proteins, in terms of folding delity or activity. However, several heterologous proteins (including an scFv)have been exported by Tat and shown to be active in previous studies [7,11,12,13] and there is no obvious reason why export mediated by the PhoDn signal should be different. Moreover, a range of studies have shown that the Tat system is predisposed to export correctly folded proteins [5][6][7][8][9][10][11][12][13][14][15][16][17][18]10].…”
Section: Discussionmentioning
confidence: 98%
“…Generally, Tat substrates only exit the cytosol once they are fully folded and contain their cofactor (138,139,140,141,142). The respective proofreading is extremely tight in B. subtilis (166,167), but 10 less stringent in the thylakoidal Tat system as unfolded proteins are also transported (35).…”
Section: Tat Proofreadingmentioning
confidence: 99%
“…The functionalities of natural systems may be harnessed, for example, by transporting man-designed elements to the desired location within the cell. In recent research the E. coli twin-arginine translocation (TAT) apparatus, whose quality control mechanism will only allow the export of fully folded proteins across the cytoplasmic membrane, could ‘read’ the folding state of a completely artificial heme-binding protein and translocate it to the periplasm [ 65 ]. While the bacterial Sec system has been proved capable of transporting de novo proteins in an unfolded state [ 24 ], the TAT system may be able to transport other de novo proteins that must fold in the cytoplasm prior to translocation.…”
Section: Fully Biocompatible De Novo Designed Proteinsmentioning
confidence: 99%